Effect of vehicle operating parameters on fuel consumption and the overall energy efficiency of the drive system - Jaroslaw Gonera; Michał Janulin; Oleksandr Vrublevskyi (Archives of Transport)
This article presents a research methodology that supplements known studies to solve the problem of a correct complementary analysis of vehicles with different drive units. This method can be used at the stage of selecting a car for specific tasks, as well as for in-service technical condition checks. A new method is proposed for analysing the impact of operating conditions on the mileage fuel consumption, unit fuel consumption and overall energy efficiency of vehicles. In the study, it was possible to determine the effect of changing the vehicle speed, road gradient angle and vehicle weight. Tests identifying fuel consumption and efficiency characteristics as a function of vehicle load were carried out using passenger cars with different drive designs. Carrying out tests under laboratory conditions on a chassis dynamometer bench enabled the precise determination of the change in operating conditions. The criteria adopted for the evaluation included fuel consumption and overall vehicle energy efficiency. The variable parameters included speed, vehicle weight, and the road gradient angle. The data for criteria calculation were acquired using a diagnostic tester with a functional parameter recording function. The application of the presented method enabled a comparison of the overall energy efficiency of two vehicles equipped with spark-ignition combustion engines, according to the criteria listed. The experiment showed that in a three-cylinder engine, unit fuel consumption is more sensitive to parameter changes under identical conditions (speed, vehicle weight, road gradient angle) than in a four-cylinder engine. To evaluate the drive units of the test vehicles, characteristics of changes in the overall energy efficiency were used as well. It was observed that in all testing variants, the value increased with increasing road gradient values, with the intensity of η increase not being constant. A car with a four-cylinder engine has a higher energy efficiency at low loads. The proposed methodology is relevant for evaluating vehicles with different drive systems (including hybrid) and adapting drive characteristics to the operating conditions. Partially the presented methodology can also be  transferred to EV vehicles - in terms of energy efficiency.